Prevalence of some species of flies in cowsheds in Mosul city - Haitham S. AlBakri; Layan Y. Khalil; Hadeel T. Al-Shalash (Iraqi Journal of Veterinary Sciences, 2023)
The flies of different families that the flies which act as the main sources of annoyance to both humans and animals, as well as being direct vectors of many pathogens, its indeed need to do this study to check for the presence of these flies within the animal environment near the sources of food and water, in addition to their presence close to animals or on their bodies. As indicated from the results of the present study of morphological or formal specification for Musca, Lucilia, Chrysoma, Stomoxys, and Parasarchophaga, which were collected from cowsheds from AL-Saada and Baawyza and Al-Shalalaat areas in Mosul city. The current study focused on the morphological features of flies collected to achieve guideline evidence with images taken under the stereoscopic dissecting microscope. Three families and seven species of dipteran flies' morphological specifications have been revealed in this research with the help of taxonomic keys particularly; wing venation, number of strips on the thorax, color of head, thorax, and abdomen with colored hairy of the flies and antennae, as well as an activity note of flies during the day and peak of this activity in the noon hours, especially in the warm months in which the study took place, like April and May and the daylight time (sunrise at 4:52-5:57 am, the sunset at 6:29-7:17 pm) characterized encouraging for light action of flies families.